Controversies Around the System, Organisation and Curriculum Structure of Secondary School Education in Poland, in the Years 1944–1948 - Gulczyńska, Justyna (Biuletyn Historii Wychowania, 2018)
A new form of government of the Polish state was combined with its rather intensive influence on the character of the educational system, including general secondary schools. That time is distinguished by numerous controversies, which then appeared in various social circles, political parties, and referred to the constitutional and organizational structure as well as the program structure of this school level. In the first years the controversies were more of an evolutionary concepts for the Polish route to socialism were still possible. After 1948 there was no more room for discussion; the decisions about this sphere were also made by one group – the people related to the communist party (Pol. abbr. PZPR). Already right after the cessation of war activities, the tendencies leading to the centralization of education management were noticeable, and consequently, ever more intense influence of the government of the working classes (lub the people’s government) on the functioning of schools, but, above all, on the teaching content. The process of centralization was linked with the so-called democratization process of school i.e., the question, of which the ruling communists made their priority. A consequence of democratization of the general secondary school and rendering it a tool for the manufacture of future citizens – devoted to and subjected to the government of the working classes – was the aspiration for closing private general secondary school, and also the expulsion of religion from school. Such changes, falsely justified by the necessity to observe the principle of freedom of conscience and confession, led to the secularization of the school system. The discussed expulsion of the Church from schools, and at the same time from the sphere of educating a young generation, was supposed to serve the formation of a new socialist society in the future.